Relativity and the Magnitude of Velocities - Ajeti, Musa; Berisha, Valbona; Klinaku, Shukri (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
In modern physics, relativity is primarily understood through the framework of Einstein’s theory. According to the special theory of relativity (STR), Galilean relativity serves as a very accurate approximation at low velocities, where ‘relativistic effects’ can be neglected. However, at high velocities, these effects become significant and are accurately described by STR. This paper challenges this understanding, arguing that the opposite is true. In Galilean relativity, the relativity of time is substantial and cannot be ignored. Thus, relative time is more negligible in STR than in Galilean relativity. By comparing Galilean relativity and STR through physical, mathematical, and specific examples, two conclusions are drawn: first, the current categorization of relativity theories based on velocity magnitude is artificial and inaccurate; second, the relativity of time can be ignored in special relativity, while it remains significant and cannot be overlooked in Galilean relativity.